"Letters to C.K. Ogden," - "Wittgenstein, Ludwig" (Oxford, 1973)
The late C.K. Ogden preserved original material of great interest relating to the publication in England of Wittgenstein's Logisch-Philosophische handling under the title: Tractatus Logico-Philisophicus. This material confirms a statement made in Ogden's prefatory note to the translation that the proofs of the translation and the version of the original which appeared in the final number of Ostwald's Annalen Der Naturphilosophie(1921) had been very carefully revised by the author himself.
Keywords: "Wittgenstein, Ludwig."